The Relationship Between Customer Perceived Value, Service Quality, Brand Trust, and Customer Retention in the Retail Industry - Wahyuni, Ira; Kusumaningtyas, Daru Putri; Mahdani, Hakkul Bahiz; Wibowo, Daniel Pungkas Prastia (IJBLE Scientific Publications Community Inc., 2024)
This study investigates the relationship between customer perceived value, service quality, brand trust, and customer retention in the retail industry. Using a quantitative approach, data were collected from 350 retail customers and analyzed using Structural Equation Modeling (SEM). The findings reveal that customer perceived value, service quality, and brand trust significantly influence customer retention, with brand trust showing the strongest effect. The combined effect of these factors explains 62% of the variance in customer retention. The results underscore the importance of an integrated approach in retail, where perceived value, high service standards, and trust are key to maintaining customer loyalty. This study provides valuable insights for retail managers aiming to enhance retention through strategic improvements in customer experience, service quality, and brand-building efforts.